Counseling College Student-Athletes: A Working Alliance Model Approach - Kissinger, Daniel B.; Watson, Joshua C. (My University, 2005)
Student-athletes often represent a highly visible, yet decidedly misunderstood population on college and university campuses. In the general student population, the combination of multiple stressors often leads students to seek professional counseling services. Unfortunately, student-athletes, who are often faced with a multitude of psychosocial stressors germane to balancing athletic and academic responsibilities, seldom seek out professional counseling services. However, when they do seek services, the authors posited that an understanding of the construct of the therapeutic working alliance and the application of the working alliance model (Bordin, 1979) offered a useful template for fostering positive counseling outcomes with student-athletes. In this article, the major elements of this construct and model were presented along with a discussion and implications for its application to a college or university student-athlete population.
Keywords: models; academic support